The Optimal Model for Consumers’ E-wallets Usage Intention - Cuong, Dam Tri (Software Engineering Application in Informatics, 2021)
These days, the entire world is getting digitalized, and payments through cell phones have become the most straightforward payment method, supplanting cash-based payment methods. The technological progressions have made it essential for the present buyers to utilize their cell phones since it is quicker, simpler, and convenient to do the everyday exchanges. In addition, the reasons (bonus points and cashback) give to the client, deciding to pay through e-wallets, pulls the clients from all age gatherings to pay through e-wallets. This study aims to empirical research for searching the optimal model to clients’ e-wallets usage intention. We implemented the Akaike information criterion (AIC) technique with RStudio software for selecting the optimal model. AIC is one of the most widely used model choice techniques in most statistical software packages. The finding reveals the best model includes determinants (effort expectancy, perceived ease to use, promotions, and perceived security and privacy) that significantly impact clients’ e-wallets usage intention.